x+19+2x=-5-2x-11

Simple and best practice solution for x+19+2x=-5-2x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+19+2x=-5-2x-11 equation:


Simplifying
x + 19 + 2x = -5 + -2x + -11

Reorder the terms:
19 + x + 2x = -5 + -2x + -11

Combine like terms: x + 2x = 3x
19 + 3x = -5 + -2x + -11

Reorder the terms:
19 + 3x = -5 + -11 + -2x

Combine like terms: -5 + -11 = -16
19 + 3x = -16 + -2x

Solving
19 + 3x = -16 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
19 + 3x + 2x = -16 + -2x + 2x

Combine like terms: 3x + 2x = 5x
19 + 5x = -16 + -2x + 2x

Combine like terms: -2x + 2x = 0
19 + 5x = -16 + 0
19 + 5x = -16

Add '-19' to each side of the equation.
19 + -19 + 5x = -16 + -19

Combine like terms: 19 + -19 = 0
0 + 5x = -16 + -19
5x = -16 + -19

Combine like terms: -16 + -19 = -35
5x = -35

Divide each side by '5'.
x = -7

Simplifying
x = -7

See similar equations:

| 13x=130-x | | 2(x-5)=3(x+2) | | 6c^2-48c+90=0 | | 2n+48=-6n | | 7(x-3)=8(x+1) | | -5(-1-2k)=85 | | -15x-20=-12x+100 | | 5(x-2)=6(x+1) | | 4(x-5)=5(x+2) | | 5(12-3w)+25w=2w | | c^2+6c+5=0 | | 272=-8(-4+6a) | | -15x-20=-2x+100 | | 252=-4(7x-7) | | 3(x-2)=4(x+1) | | 18-5x=12+x | | 5(12-3w)+25=2w | | 4r=48 | | 243=27r | | 3x-9=4x | | 5(12-3)+25=2w | | 5x-8=7x | | -2+6n=-80 | | 4x=2x+19 | | ag-14=2g | | 5(x+2)+8=28 | | 49x^2=28x-4 | | 6x^2-15x+14x-35=0 | | 2(x+5)+7=19 | | 5x+4=3x+2 | | -2+6n=-8 | | 3(x+4)+8=2 |

Equations solver categories